Insulin Requirement and Complications Associated With Serum C-Peptide Decline in Patients With Type 1 Diabetes Mellitus During 15 Years After Diagnosis - Suh, Junghwan; Lee, Hae In; Lee, Myeongseob; Song, Kyungchul; Choi, Han Saem; Kwon, Ahreum; Kim, Ho-Seong; Chae, Hyun Wook (Frontiers in Endocrinology, 2022)
Objective: C-peptide is conventionally used in assessing pancreatic function in patients with diabetes mellitus. The clinical significance of this molecule during the course of type 1 diabetes mellitus (T1DM) has been recently revisited. This study aimed to investigate the natural course of C-peptide in T1DM patients over the period of 15 years and analyze the association between the residual C-peptide and diabetes complications. Methods: This retrospective study included a total of 234 children and adolescents with T1DM. Patient data including sex, age at diagnosis, anthropometric measures, daily insulin dose, serum HbA1c, post-prandial serum C-peptide levels, lipid profiles, and diabetic complications at the time of diagnosis and 1, 3, 5, 10, and 15 years after diagnosis were retrospectively collected. Results: Among the 234 patients, 101 were men and 133 were women, and the mean patient age at initial diagnosis was 8.3 years. Serum C-peptide decreased constantly since the initial diagnosis, and showed a significant decline at 3 years after diagnosis. At 15 years after diagnosis, only 26.2% of patients had detectable serum C-peptide levels. The subgroup with older patients and patients with higher BMI standard deviation score showed higher mean serum C-peptide, but the group-by-time results were not significant, respectively. Patients with higher serum C-peptide required lower doses of insulin and had fewer events of diabetic ketoacidosis. Conclusion: Serum C-peptide decreased consistently since diagnosis of T1DM, showing a significant decline after 3 years. Patients with residual C-peptide required a lower dose of insulin and had a lower risk for diabetic ketoacidosis.